KEGIATAN PKM PENERAPAN NILAI INTEGRITAS MENUJU WBK DI PROGRAM STUDI AGRIBISNIS UNIVERSITAS SAMUDRA - Safrizal; Iswahyudi; Kasaf, Michel; Mahdi, Saiful; Hadisugelar, Danar; Alfisyahrin; Arief Diana, Muhammad (Fakultas Teknik, Universitas Samudra, 2025)
This community service activity aims to implement the Integrity Zone (ZI) initiative towards establishing a Corruption-Free Zone (WBK) within the Agribusiness Study Program of the Faculty of Agriculture at Samudra University. The primary issue addressed is the absence of ZI implementation, which poses a risk to transparency, accountability, and the quality of governance within the program. The methods employed include preliminary discussions, focus group discussions (FGDs), the provision of complaint boxes and online reporting platforms, seminars/workshops, the installation of informational banners (x-banners), and activity evaluations. The outcomes of the activity indicate a 26% increase in participants’ understanding of integrity values, the establishment of a complaint mechanism, and the formulation of a draft joint commitment to ZI. This initiative has had a positive impact on fostering a culture of integrity and enhancing the quality of public service. The success of the program demonstrates that collaborative and educational approaches are effective in promoting governance reform within higher education institutions.